2020
DOI: 10.1007/s00264-020-04645-3
|View full text |Cite
|
Sign up to set email alerts
|

A clinical pathway for pre-operative screening of COVID-19 and its influence on clinical outcome in patients with traumatic fractures

Abstract: Purpose Coronavirus disease 2019 (COVID-19) has become a worldwide pandemic. The toughest issue traumatic orthopaedic surgeons are faced with is how to maintain a balance between adequate COVID-19 screening and timely surgery. In this study, we described our experience with pre-operative COVID-19 screening in patients with traumatic fractures. Furthermore, we analysed the clinical results of fracture patients undergoing confined or emergency surgery during the COVID-19 outbreak. Methods This was a case series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
(22 reference statements)
1
34
1
1
Order By: Relevance
“…Spain is currently expected to be the country with the most elderly population in the world by 2040 [9]. As it has been already reported, despite the contingency plans and lockdown measures, the incidence of osteoporotic hip fractures seemed to remain stable during the State of Emergency (implementation of stringent lockdown measures for the population) [10,11]. In the present study, proximal femoral fracture was the most common reason for admission (33.8%).…”
Section: Discussionsupporting
confidence: 65%
“…Spain is currently expected to be the country with the most elderly population in the world by 2040 [9]. As it has been already reported, despite the contingency plans and lockdown measures, the incidence of osteoporotic hip fractures seemed to remain stable during the State of Emergency (implementation of stringent lockdown measures for the population) [10,11]. In the present study, proximal femoral fracture was the most common reason for admission (33.8%).…”
Section: Discussionsupporting
confidence: 65%
“…The findings of this study are alarming, as about onethird of sampled dentists reported that there was no work plan, or they were unaware that there was a work plan for COVID-19 patient screening and dental management in their practices. Proper channeling of patients using a clear work plan for COVID-19 was an essential element in guidelines proposed by some international health organizations [29,30]. It has been recommended to use tele-screening for patients to avoid contact with patients who could be a source of infection to the dental office staff and other patients [18,29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Proper channeling of patients using a clear work plan for COVID-19 was an essential element in guidelines proposed by some international health organizations [29,30]. It has been recommended to use tele-screening for patients to avoid contact with patients who could be a source of infection to the dental office staff and other patients [18,29,31]. It is not surprising that more than half of the participating dentists in this study responded that their practices did not employ tele-screening for patients before their dental visits, as it requires extra-staff with special training to conduct such tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This is already happening in some places, and although preoperative screening will potentially increase the time between admission and surgery, initial evidence suggests that this risk can be minimised to the point that it can be balanced against the potential risk of performing surgical procedures in COVID-19 patients. 51 Further research is necessary to establish whether the testing pathway is of more clinical benefit than not having it. In patients with suspected or confirmed COVID-19, the COVID-19 status of newborns should also be taken into account where relevant.…”
Section: Discussionmentioning
confidence: 99%